2014
DOI: 10.1039/c4ra07467j
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondria-targeted fluorescent probe based on TPP-conjugated carbon dots for both one- and two-photon fluorescence cell imaging

Abstract: A simple approach of a mitochondria-targeted fluorescent probe has been demonstrated for the preparation of highly water-soluble and fluorescent TPP-conjugated carbon dots (TPP-CDs) derived from lowcost citric acid and urea. We found that the TPP-CDs are suitable for both one-and two-photon mitochondria-selective imaging in living cells.Scheme 1 Schematic illustration of the synthesis of N-doped TPP-CDs for mitochondria-targeted cell imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 17 publications
1
61
0
Order By: Relevance
“…Besides targeting the specific cells, high selectivity on the organelle is another way to achieve the targeting function. Wang et al [113] have selected the triphenyl phosphonium (TPP) head groups as the targeting moiety to deliver the fluorophore to mitochondria, where these lipophilic cations can selectively accumulate in the organelle due to the large membrane potential gradient [114]. The TPP was chemically linked with fluorescent CDs, which results in the TPP-CDs has higher accumulation on the mitochondria than the non-conjugated CDs.…”
Section: Fluorescent Cds Conjugated With Targeting Unitmentioning
confidence: 99%
“…Besides targeting the specific cells, high selectivity on the organelle is another way to achieve the targeting function. Wang et al [113] have selected the triphenyl phosphonium (TPP) head groups as the targeting moiety to deliver the fluorophore to mitochondria, where these lipophilic cations can selectively accumulate in the organelle due to the large membrane potential gradient [114]. The TPP was chemically linked with fluorescent CDs, which results in the TPP-CDs has higher accumulation on the mitochondria than the non-conjugated CDs.…”
Section: Fluorescent Cds Conjugated With Targeting Unitmentioning
confidence: 99%
“…With many functional groups on the surface (such as amino, carboxyl, or hydroxyl), they can carry different therapeutic agents by means of covalent bonding or electrostatic interaction (Mewada et al 2014;Wang et al 2014a, b). Doxorubicin (DOX) is an effective chemotherapeutic agent that is commonly used for different cancers, including cervical carcinoma, the aggressive lymphoma, breast cancer and others (Liu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous natural and synthetic, graphite and organic substances have been explored for the fabrication of CDs with various routes, such as oxidization by-products of carbon nanotubes and graphite (Tao et al 2011) and candle soot (Liu et al 2007), hydrothermal cracking or microwave assisted synthesis of organic compounds (Sahu et al 2012;Yang et al 2012). Due to their unique properties, CDs have increasingly shown potential in broad applications including energy conversion , environmental analysis and bioanalysis (Costas-Mora et al 2014;Liu et al 2012), sensors (Gao et al 2014), diagnostics (Posthuma-Trumpie et al 2012) and bioimaging (Wang et al 2014a, b).…”
Section: Introductionmentioning
confidence: 99%
“…212 According to the experimental results and theoretical simulations, they found that graphitic-C 3 N 4 QDs emit strong blue fluorescence at 400 nm and green emission under one-photon UV excitation and two-photon excitation at 780 nm. In addition to these successful syntheses of carbon-based QDs, the conduction of TPF microscopy made water-dispersed and biocompatible carbon QDs, which might offer new advantages in biosensing, drug delivery, two-photon photodynamic cancer therapy, 213 cellular tracking 212,214,215 and deep-tissue imaging. 209 Ray et al also reported that graphene oxide featured an extremely high 46 890 GM of TPA for selective two-photon imaging of SK-BR-3 breast tumor cells.…”
Section: Nir-absorbing Organic Materials: Dyes and Polymersmentioning
confidence: 99%